Pengaruh Kombinasi Akupresur dan Aromaterapi Peppermint Terhadap Nausea Pada Pasien Post SC: Effect of Combination of Acupressure and Peppermint Aromatherapy on Nausea in Post SC Patients - Restu Luhwi Yuniarti; Fitriana Kurniasari Solikhah; Sulastyawati Sulastyawati; Naya Ernawati (Jurnal Keperawatan Terapan, 2024)
Nausea is a side effect after surgery that usually occurs and is often complained of. The incidence of post-cesarean section nausea currently ranges from 30-80%. One non-pharmacological method that can reduce nausea is a combination of acupressure and peppermint aromatherapy. Acupressure is a massage method from China which is carried out by pressing the Pericardium-6 area, while peppermint aromatherapy is an essential oil derived from peppermint leaves containing menthol which is then inhaled. This study aims to determine the effect of a combination of acupressure and peppermint aromatherapy on nausea in post-SC patients. This research method uses a quasi-experimental design with purpose sampling technique. The sample size was 32 respondents who were divided into 2 control and treatment groups, each group containing 16 respondents. This research uses the Wilcoxon and Man-Whitney tests. The results of the research in the treatment group after being given intervention for 10 minutes showed that there was a significant change with a p-value of 0.000 (<0.05). The conclusion of this study is that the combination of acupressure and peppermint aromatherapy has a significant effect on reducing nausea in post-SC patients. It is hoped that health workers can apply a combination of acupressure and peppermint aromatherapy to reduce nausea in post SC patients.Keywords: Post SC, Nausea, Peppermint Aromatherapy, Acupressure.